Sensitivity of two-tier and three-tier tests in detecting student’s misconceptions of chemical bonding - Ebiati Ebiati; Asrial Asrial; Muhammad Haris Effendi-Hasibuan (Pascasarjana Universitas Negeri Medan, 2020)
This research study aims to determine how the sensitivity of two-tier and three-tier tests in detecting student’s misconceptions about chemical bonding. This research is a quantitative study with a total sampling technique that is measured using three-tier multiple-choice with a modified CRI. Based on the findings, with a two-tier multiple-choice, the percentage value of the understanding category is 86.06%, misconceptions are 6.89%, and do not understand is 7.06%. Meanwhile, using a three-tier multiple-choice, the percentage value of the understanding category is 85.33%, misconception amounted to 7.61%, and did not understand 7.06%. This study concludes that three-tier multiple-choice is more sensitive than two-tier multiple-choice in detecting students' misconceptions of chemical bonding. Keywords: Chemical bonding, Misconception, Three-tier, Two-tier